Organ Homologies and Perianth Evolution in the Dasymaschalon Alliance (Annonaceae): Inner Petal Loss and Its Functional Consequences - Guo, Xing; Thomas, Daniel C.; Saunders, Richard M. K. (Frontiers in Plant Science, 2018)
The Dasymaschalon alliance within the early-divergent angiosperm family Annonaceae comprises c. 180 species in four genera (Dasymaschalon, Desmos, Friesodielsia and Monanthotaxis). The alliance offers an excellent opportunity for investigating perianth evolution and functional adaptations because of the presence of different numbers of petal whorls and contrasting floral chamber morphologies. The absence of the inner petal whorl in Dasymaschalon renders it distinctive in the family: previous studies have suggested that its three outermost stamens might be homologous with the inner petals of the sister genus, Friesodielsia, reflecting a homeotic shift of floral organ identify from inner petals to stamens. To investigate this hypothesis and general perianth evolution in the alliance, we (i) compared the floral vascularization of selected Dasymaschalon and Friesodielsia species using paraffin serial sectioning, and (ii) mapped selected perianth characters of inferred functional significance onto a molecular phylogenetic framework of the Dasymaschalon alliance (46 accessions; five cpDNA, and two nrDNA markers). The results indicate that the vasculature of the outermost stamen whorl of Dasymaschalon does not fuse with the perianth cortical vascular system, but instead splits from the basal traces of the free stamen bundles, contradicting previous inferences of homology with the inner corolla whorl of other Annonaceae. The loss of the inner petal whorl in Dasymaschalon is less likely to be due to a homeotic mutation, and instead possibly involved either the loss of genes that are responsible for determining inner petals or else the expression failure of these genes. Optimizations of perianth characters indicate that the absence of the inner petal whorl and the connivence of outer petals during anthesis are synapomorphic for Dasymaschalon. Circadian trapping of pollinators is inferred either to be derived in the stem lineage of the Dasymaschalon-Friesodielsia clade, or else to have evolved in parallel in the Dasymaschalon and Friesodielsia lineages. Subsequent changes in the remaining petals of Dasymaschalon flowers (which do not fully separate during anthesis) are likely to have enabled perpetuation of the circadian trapping mechanism, lessening the adverse impacts of inner petal loss.